Malpractice and Avascular Necrosis: Legal Outcomes - Rose M Carter (Canadian Journal of Gastroenterology)
Every physician, but particularly specialists, have reason to be concerned about medical legal issues. Avascular necrosis has been established as a possible serious complication of steroid treatment in inflammatory bowel disease. Two specific Canadian cases illustrating the sequence of medical history, time, expert testimony and legal outcomes are presented. Awards plus costs in the order of $1 million or more were the result of these legal proceedings. The courts stated the major factors in finding liability against doctors were the failure to show the patient had been fully informed of treatment options. There was considerable weight given to expert testimony and the patient recollection of events to support their contentions. Adequate contemporaneous record keeping was absent to contradict evidence of the patients. The judges in both illustrative examples leaned heavily on Supreme Court of Canada guidelines whereby the patient must be informed at all stages of the medical process.